Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

x/3-x/2=6 x/3-x/2=6 x/3-x/2=6 x/3-x/2=6 x/3-x/2=6 x/3-x/2=6 x/3-x/2=6

 x/3-x/2=6
 x/3-x/2=6
 x/3-x/2=6
 x/3-x/2=6
 
 x/3-x/2=6
 x/3-x/2=6
 x/3-x/2=6

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
11 months ago
Dear Student

6x – 9 -2(1+x) = x -9

6x -9 -2 – 2x = x – 9

6x – 2x – x = -9 + 9 + 2

3x = 2

x = 2/3

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free